Indoor infrared wireless communication channels. - Pakravan, Mohammad Reza. (University of Ottawa (Canada), 2000)
The emergence of portable computing devices is expected to accelerate the introduction of wireless Local Area Networks (LANs). Portable devices require connectivity with low power consumption, small size and weight. The demand for inexpensive, high-speed communication links satisfying these requirements his encouraged the research on infrared wireless communications. In this thesis, the fundamentals of infrared communications and different suitable configurations are reviewed. The basic nature of the infrared channel, the differences between the infrared channel and radio frequency channel and the important communication problems faced by infrared systems are explained. An infrared channel simulation algorithm that is used to estimate its impulse response is described. An extensive set of measurements has been performed to investigate the effects of receiver rotation, receiver shadowing, receiver displacement, transmission configuration and communications environments on the characteristics of the infrared channel. The characteristics of the wide-band measurement system that was used to collect the infrared channel transfer functions are presented. The objectives, procedures, results and conclusions of these measurements are discussed and reported. Diffusers are an important element of infrared transmission systems. They are used to control the radiation pattern of the transmitter for efficiency and eye-safety. Holographic diffusers have been designed and manufactured to provide better infrared radiation patterns. These diffusers were used in the measurement setup to assess the performance enhancements that can be achieved by using holographic diffusers. The results show uniform and efficient use of optical power and better tolerance to shadowing by using these devices.
Keywords: Engineering, Electronics and Electrical.